2021
DOI: 10.2172/1840202
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Data Assessment for Advanced Reactors

Abstract: Advanced reactor concepts being developed throughout the industry are significantly different from light-water reactor (LWR) designs with respect to geometry, materials, and operating conditions, and consequently, with respect to their reactor physics behavior. Given the limited operating experience with non-LWRs, the accurate simulation of reactor physics and the quantification of associated uncertainties are important for ensuring that the nuclear design for advanced reactor concepts include appropriate marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Based on previous studies [2], the effect of nuclear data library changes is expected to be negligible for reactivity coefficients. Therefore, all other reactivity calculations presented in this section were performed only with ENDF/B-VII.1.…”
Section: Eigenvaluementioning
confidence: 92%
See 1 more Smart Citation
“…Based on previous studies [2], the effect of nuclear data library changes is expected to be negligible for reactivity coefficients. Therefore, all other reactivity calculations presented in this section were performed only with ENDF/B-VII.1.…”
Section: Eigenvaluementioning
confidence: 92%
“…Although validation has been focused on water-moderated thermal spectrum systems, criticality validation also includes systems of intermediate and fast spectral conditions [28]. Previous SFR development and analysis efforts with SCALE included the analysis of the EBR-II [3] and the 1,000 MWth Advanced Burner Reactor benchmark [2], as well as the generation of MG nuclear data libraries specifically for SFRs [4] and fast reactors in general [10].…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions were drawn upon the fact the INL Design A is a fast spectrum system based on 235 U-enriched fuel. The top contributors of mixed U/TRU-fueled fast spectrum reactors (such as those assumed in SFRs) do not include 235 U (n,γ) as the dominant contributing reaction (Bostelmann et al, 2021b).…”
Section: Inl Design Amentioning
confidence: 99%
“…This paper provides a summary of key observations and conclusions obtained during this study, while providing just two examples to demonstrate how the computational analyses were performed. Detailed analysis results are available in a comprehensive technical report (Bostelmann et al, 2021b) issued by the NRC. It is noted that the study focused on systems with 235 U enriched or mixed uranium/plutonium fuel based on spent LWR fuel; 233 U-fueled systems were not considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear data uncertainty is propagated to all nuclear-related figures of merit of reactors such as k-eff, void, temperature and power reactivity coefficients and reactivity worth's. In a recent assessment of the nuclear data needed for advanced reactors, it was found that for several nextgeneration reactors need better resolved nuclear data (Bostelmann, et al, 2021). For example, in a sensitivity analysis of the Advanced Burner Reactor 1000 MWth Reference Concept, it was shown that the uncertainty in important nuclear characteristics is driven by uncertainties in uranium, plutonium, iron and sodium.…”
Section: Fast Neutron Sourcementioning
confidence: 99%